(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main sentence of the poem ’I arrived’ by Kamala Das is, ’I am what I am." She says she doesn’t care about politics or who is the leader, but she knows all about all the politicians from Nehru to the present day. Her message read like she was trying to explain to everybody out there that it’s not her fault that some things of her upbringing will be a part of her subconsciousness, whether she wants it or not. Kamala Das stands out as a prominent feminist figure of the post-colonial period. She wrote both in Malayalam (her maternal language) and in English too. Similarly, she followed a different pen name for Malayalam and English audiences and used Madhavi Kutty when she wrote in Malayalam and Kamala Das when she wrote in English. Modern Indian English poetry is enriched and beautified by her outstanding contributions, which have also earned her the honorific title "The Mother of Modern Indian English Poetry" for any reason. She has been attributed to the same level of knowledge as literary magnificence like Sylvia Plath because she unmasks her feelings. On the day we are reminded of her birth, we also go back in time and see how this famous author has created a world of her own and is creative in every piece of writing. The great Kamala Das is perhaps the most prominent character in Indian English poetry. She is at the top of the list of sources of inspiration for Indian English poetry. In reality, The Times even conferred on her the title “mother of modern Indian English poetry” (www.timesonline.co.uk) in 2009. She wrote a total of three poems in order to highlight the fact that these politicians were sleeping and woke up in the same repetitive cycle of history. By humanising the lines, they are made more engaging for reading and fully understandable for listeners. Not the community of antiquity alone; time defined who they were. The essay is identified as a research work that stresses the significance of Sinha in Indian English poetics.